Protective Effects of Sapindus Saponins in Spontaneously Hypertensive Rats - 陈明 陈志武 龙子江 王举涛 王雅娟 刘金林 (Chinese journal of integrative medicine, 2015)
Objectives： To investigate the protective effects of Sapindus saponins in spontaneously hypertensive rats, and the possible cellular and molecular mechanisms. Methods： Thirty-two 16-week-old spontaneously hypertensive rats were randomly divided into four groups （8 in each group）： model group （placebo）, positive control group （27 mg/kg of Captopril Tablets）, Sapindus saponins groups （27 mg/kg and 108 mg/kg, respectively）. Another 8 healthy Wistar-Kyoto strain （WKY） rats were used as the normal group. The animals were treated for 8 weeks. Blood pressure of rats was determined by non-invasive blood pressure meter （BP-6）. Furthermore, the contents of angiotensin Ⅱ （Ang Ⅱ） in plasma and myocardial tissue were determined by enzyme-linked immunosorbent assay （ELISA）, the gene expression of receptor angiotensin type 1 （AT1R） in aorta was determined by quantitative real- time polymerase chain reaction （qRT-PCR）. The protein expression of transforming growth factor- β1 （TGF- 1β1） and AT1R in heart was determined by immunohistochemical staining. The protein expression of p-phosphorylation of p38 mitogen-activated protein kinase （p-p38MAPK） was determined by Western blotting. The contents of interleukin （IL）-1, IL-6 and tumor necrosis factor （TNF） in serum were determined by radioimmunoassay. And the histopathological and morphological changes of aorta and heart tissue samples were assessed semi-quantitatively by hematoxylin-eosin （HE） or Masson staining. Results： Thirty minutes after single or continuous treatment, systolic blood pressure （SBP） was reduced significantly in Sapindus saponins groups. And the contents of Ang 11, IL-1, IL-6 and TNF-α in serum, the expression of AT1R mRNA, p-p38MAPK and TGF- β1 were significantly suppressed dose-dependently （P〈0.05 or 1=〈0.01）. With the Sapindus saponins treatment, compared with those of the model group, the cardiac and aortic pathological changes were ameliorated significantly. Conclusions： Our findings suggest that Sapindus saponins might have protective effects in spontaneously hypertensive rats, the cellular and molecular mechanisms of which might be relevant to the regulation of inflammatory responses mediated by p-p38MAPK signal pathway based on activated Ang Ⅱ and AT1R.